State General Revenues and Expenditures in Florida - David Mulkey; Henry Cothran (EDIS)
This is EDIS document FE366, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published December 2002.